Anti-nociceptive effect of Caralluma edulis on peripheral and central pain pathways - Firdoos, Sundas; Khan, Arif-Ullah; Ali, Fawad (Penerbit Universiti Kebangsaan Malaysia, 2017)
The purpose of the present research was to evaluate the phytochemical content and analgesic effect of Caralluma edulis (Ce.Cr). Established methods were used for phytochemical analysis of plant. The anti-nociceptic activity of Ce.Cr was scrutinized using acetic acid-induced writhings, tail immersion and hot plate methods. Ce.Cr was tested positive for the presence of therapeutically active metabolites such as alkaloids, flavonoids, glycosides, phenol, tannins, terpenoids and saponins. Ce.Cr at the dose of 10, 30 and 100 mg/kg inhibited acetic acid-induced abdominal writhes and increase the latency time to thermal stimuli in both tail immersion and hot plate tests, similar to standard drug. These results showed that the ethanolic extract of Caralluma edulis possesses anti-nociceptive property.